Increases in Cognitive Activity Reduce Aging-Related Declines in Executive Functioning - Stieger, Mirjam; Lachman, Margie E. (Frontiers in Psychiatry, 2021)
Declines in cognitive functioning are commonly experienced with aging, yet there is wide variation in the nature and extent of these changes. Previous research has shown associations between the frequency of engaging in stimulating cognitive activities and performance on cognitive tests. However, it is not known whether it is important to increase the amount of cognitive activity as one gets older in order to curtail cognitive declines. We examined cognitive activities and cognition in a national sample of 2,130 community-dwelling middle-aged and older adults from the Midlife in the United States longitudinal study. Participants completed cognitive assessments of episodic memory (EM) and executive functioning (EF) on two occasions, approximately nine years apart. At the first assessment, participants ranged in age between 33 and 83 years (M = 55.76, SD = 11.09), with 56.1% women. Multilevel models were tested to examine educational level and change in cognitive activity as predictors of change in EM and EF, controlling for initial level of cognitive activity and key correlates of cognitive decline. Results indicated that increases in cognitive activity were important over and above earlier levels of cognitive activity for reducing declines in EF. Further analysis also showed differential results by educational level. Increased cognitive activity was not associated with changes in EF among individuals with a college degree. In contrast, individuals without a college degree who increased their cognitive activity showed significantly less decline in EF compared to those without a college degree who decreased or maintained their cognitive activity across the nine years. Thus, the results suggest that increased engagement in cognitive activity makes more of a difference for EF declines among those without a college degree. The results have particular relevance given that aging-related changes in domains such as work status, health, or social relationships can lead to reductions in stimulating cognitive activities. The findings emphasize the importance of increasing cognitive activities especially among those with lower educational attainment.